THE STUDY OF THE TYPES OF INHERITANCE OF PLANT HEIGHT OF WINTER SOFT WHEAT HYBRIDS F2 - О. A. Nekrasova; P. I. Kostylev; O. V. Skripka; E. I. Nekrasov (Зерновое хозяйство России)
The plant height is an important qualitative trait. It affects productivity and resistance to lodging of the crop. The efficiency of the selection of the plants with necessary stem height depends on the amount and quality of the accumulated information about genetic system of trait control. The article deals with the results of the study of winter soft wheat hybrids of the second generation, allelic differences of the genes of plant height of four varieties. There were studied 10 hybrids F2 obtained from diallel hybridization of the varieties and lines of winter soft wheat 'Bunchuk', 'Kipchak', '1421/06' (with a working name Luiza) and '696/98' (with a working name Emma). The genetic analysis of the quantitative trait of a stem height was carried out with the help of the computer programs Gen-3 and Plygen A. The analysis determined the partial and incomplete dominance of the large value of the trait, the degree of the dominance (hp) varied from 0.12 to 0.95. It was established that the plant height differences among the studied varieties of winter soft wheat were caused by the small amount of the genes with various strength, i.e. 1-3 pairs, responsible for the transfer of the studied trait. The strength of the gene was 4, 7 and 15 cm. The varieties 'Bunchuk' and 'Kipchak', 'Kipchak' and 'Luiza', 'Luiza' and 'Emma' differed from each other according to the allelic state of one locus. The varieties 'Bunchuk' and 'Luiza', 'Kipchak' and 'Emma' differed from each other according to the allelic state of two locuses. The varieties 'Bunchuk' and 'Emma' differed from each other according to the allelic state of three locuses.